2003
DOI: 10.1088/0953-8984/15/6/302
|View full text |Cite
|
Sign up to set email alerts
|

Cation coordination in oxychloride glasses

Abstract: Glasses containing mixtures of cations and anions of nominal compositions [Sb 2 O 3 ] x -[ZnCl 2 ] 1−x where x = 0.25, 0.50, 0.75, and 1.00, have been studied by means of neutron diffraction and Raman and Mössbauer spectroscopy. There is preferential bonding within the system with the absence of Sb-Cl bonds. Antimony is found to be threefold coordinated to oxygen, and zinc fourfold coordinated. The main contributing species are of the form [Sb(OSb) 2 (OZn)] and [Zn(ClZn) 2 (OSb) 2 ].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…as demonstrated by Debenedetti and co-workers. 39,40 However, the contracted tetrahedral bonding angle observed in the antimony oxides (921 from the work of Johnson et al, 41 and 95.61 in our simulations) imposes a technical limitation in distinguishing tetrahedral and octahedral motifs in a manner similar to e.g. ref.…”
Section: Resultsmentioning
confidence: 52%
“…as demonstrated by Debenedetti and co-workers. 39,40 However, the contracted tetrahedral bonding angle observed in the antimony oxides (921 from the work of Johnson et al, 41 and 95.61 in our simulations) imposes a technical limitation in distinguishing tetrahedral and octahedral motifs in a manner similar to e.g. ref.…”
Section: Resultsmentioning
confidence: 52%
“…The compositions are given in atomic% in order to allow comparison of the losses occurring during melting. X-ray diffraction confirmed the glassy nature of the samples and 121 Sb Mössbauer spectroscopy confirmed that antimony was present in the trivalent Sb 3+ state only [1].…”
Section: Resultsmentioning
confidence: 71%
“…This makes the task of assigning peaks a simpler job. The distinguishable peaks were fitted with deconvoluted Gaussians (representative fits have been previously shown [1]) from which the peak positions and co-ordination numbers are derived. These are summarized in table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations